The case of the disappearing aneurysm - spontaneous regression of a mycotic hepatic aneurysm secondary to intravenous drug use: a case report and literature review - Green, Ryan J.; Caufield, William; Scott, Luke; Kirkham, Corey; Hinzner, Catherine; Belaguthi, Priyanka; Clarke, Ethan; Sweeney, Henry; Vennam, Sarath (International Surgery Journal, 2025)
Hepatic artery aneurysms are a rare but potentially life-threatening vascular lesion which require urgent diagnosis and management. This case report and literature review highlights the case of a 41-year-old female with a history of intravenous drug use who developed a 14 mm mycotic hepatic artery aneurysm after being treated for infective endocarditis. The patient initially presented with fever and abdominal pain. Bedside echocardiogram demonstrated valvular vegetations requiring emergent metallic valvular replacement. During the patient’s admission they developed further sequelae from endocarditis including splenic capsular rupture, renal infarcts and eventually hepatic artery aneurysm. This patient’s hepatic artery aneurysm spontaneously thrombosed over less than a week and regressed without surgical or endovascular intervention. This case is not only the first documented case of spontaneous regression of mycotic hepatic artery aneurysm but highlights the importance of considerations for acute abdominal pain in those with a history of intravenous drug use and concomitant infective endocarditis. It also demonstrates the possibility of conservative management in visceral artery aneurysms.